Performance of inventory turnover and sales growth on food and beverage profit of the company - Pradnyani, Ni Luh Putu Lely; Astawa, I Ketut; Susanto, Budi; Sukmawati, Ni Made Rai; Hakim, Jumhur (Journal of Commerce, Management, and Tourism Studies, 2023)
The study was conducted to analyse the effect of inventory turnover and sales growth on food and beverage profit at the company partially and simultaneously. This research uses a theoretical base and relevant concepts, namely the theory of inventory turnover, sales growth and food and beverage profit. This quantitative research using the analytical method namely multiple  correlation analysis, classic assumption test, multiple linear regression analysis, hypothesis test (t-test, F-test, and coefficient determination), and predictor contributions. The results indicate that the t-count value of inventory turnover is smaller than t-table (0,901 < 2,035) with a significant value more than 0,05 (0,374 > 0,05). The t-countvalue of sales growth is greater than t-table (5,901 > 2,035) with a significant value less than 0,05 (0,000 < 0,05). The inventory turnover has a positive but not significant effect on food and beverage profit at The companywith a contribution of 4,576%. Sales growth has a positive and significant effect on food and beverage profit the compa ny with a contribution of 55,224%.